Peru, mountains and los niños: Dialogic action, accounting and sustainable transformation. (December 2015) - Contrafatto, M.; Thomson, I.; Monk, E.A.
Highlights: How and why a dialogic activism project was implemented to transform a community. How accounts helped to make sustainability issues familiar for the community. Sustainable transformation praxes in school and community were found. Children' accounts mediated between sustainability and the community's needs. How dialogic accounts can be used in activist projects to improve sustainability. Abstract: In this paper we explore how accounts co-produced by Peruvian pupils and teachers, embedded within an activist project, helped to translate sustainability into something familiar that their community could engage with and act for (Contrafatto, 2013 ). Creating this closeness to, and everydayness of, sustainability was seen to be critical for community praxes. This paper presents our justification for including these children's accounts in the assemblage of practices that make up the social accounting project. We argue that it is important that sustainability accounts codify, using culturally relevant media, language and objects/symbols, the causes of a community's unsustainability in order to enable the exploration of more sustainable ways of living. The co-production of accounts with those seeking to provide locally relevant solutions is also an important aspect of sustainability accounting. This research contributes to social and environmental accounting by exploring theoretically and empirically how dialogically-inspired accounts could be used within activist projects to improve the sustainability of communities.